(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT: Camat position as a leader in the district and at the same time as the head of the working area districts have an important role and ultimately determine the manifest good govenance in the district, but in fact good govenance not been optimally realized in the district. This study intended to find out how camat role in achieving good Governace in the district of Minahasa district Tombatu southeast. The research method used is qualitative method. camat role in achieving good governance fi view of three aspects, namely pernan coordinate, direct, and supervise government in the district. informants in this study as many as 15 people were taken from the element of government officials, elements of SKPD and vertical institutions in the district, the village government elements, and organisa civic or community leaders. a key instrument in this study is the researchers themselves, while collecting data using interview techniques. Data analysis was performed using analysis models interkatif qualitave analysis of miles and hubernann. The results of data analysis that addressed the role camat coordinate, direct and supervise activities in the district administration to achieve good governance is done properly and effectively in Kecamtan Tombatu. Based on the research results deduced that camat the position / positions, duties and authorities coordinate, direct and supervise the government penyelenggraan in districts having a crucial role in achieving good governance. Departed from the conclusions of the study put forward suggestions: camat must optimize the use of means of organizing pemerintaha coordination of all work units pemetintah; optimizing the potential and the ability to provide guidance to government work units in the working area districts; and optimize the existing control facilities such as reporting systems, and monitoring and evaluation system. Key words: the role of the subdistrict head, good governance